Ethanol crude leaf extract of weeping fig (Ficus benjamina) causes mild hepatotoxicity in Sprague dawley rats - Mfoniso Iniobong Udonkang; Lynette Umasoye Douglas; Raymond Ekong Eworo (Universitas Nahdlatul Ulama Surabaya, 2024)
Weeping fig (Ficus benjaminaeaf extract has diverse medicinal properties but little is reported about its hepatotoxicity. This study determined the mean lethal dose (LD50) and investigated the effects of F. benjamina ethanol crude leaf extract on biochemical parameters and liver histology of Sprague Dawley rats. Twenty-nineemale rats weighing 133-204 g were used. The LD50 was determined with nine rats based on Lorke’s method. The experimental groups consisted of twenty rats, divided into four groups of five. Each group received treatment as follows: Control (feed and water only) and low, medium, and high doses (500, 1000, 1500 mg/kg respectively) of the extract orally for 21 days. All animals were weighed and sacrificed using Ketamine intra-peritoneal injection. Blood samples were collected for biochemical parameters of total bilirubin, conjugated bilirubin, aspartate aminotransferase (AST) alanine aminotransferase (ALT), and alkaline phosphatase (ALP). Liver tissues were removed and processed by the formalin-fixed-paraffin wax-embedding method. The tissue blocks were sectioned and subjected to Hematoxylin/Eosin and Masson trichrome staining. The extract’s LD50 was >5000 mg/kg. The rats’ body weights did not change statistically (p=0.985). Total bilirubin (p=0.003), conjugated bilirubin, AST, ALT, and ALP values (p=0.001) increased significantly. The AST high-doseroup had the highest fold increase (4.8). The liver histology showed mild sinusoidal dilation at 500 mg/kg. There was marked hemorrhage and fibrosis at medium and high doses. Although the extract had relatively low acute toxicity, 1000 and 1500 mg/kg doses were associated with mild hepatotoxicity characterized by veno-occlusion disease. The 500 mg/kg dose is safer for medicinal purposes.